PENGARUH KEPEMIMPINAN, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA ZAHRA SPA NUSA DUA - Ni Made Satya Utami; Putu Ayu Sintya Saraswati; Ni Luh Purnama Dewi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Good employee performance is a step towards achieving organizational goals, so efforts need to be made to improve employee performance. This research aims to determine the influence of leadership, motivation and organizational culture on employee performance. This research was conducted at Zahra Spa Nusa Dua. The sample in this study was 41 people who were employees of Zahra Spa Nusa Dua. The sampling method in this research is the saturated sampling method or census method. Data collection was carried out through observation, documentation, interviews and questionnaires. The data analysis technique used in this research is linear regression analysis using the SPSS version 26 program. Based on the results of the analysis, this research shows that leadership has a positive and significant effect on employee performance at Zahra Spa Nusa Dua. Motivation has a positive and significant effect on employee performance at Zahra Spa Nusa Dua. Organizational culture has a positive and significant effect on employee performance at Zahra Spa Nusa Dua.